2011
DOI: 10.1002/ptr.3693
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity‐guided Isolation of Cytotoxic Sesquiterpene Lactones of Gochnatia polymorpha ssp. floccosa

Abstract: Phytochemical study of Gochnatia polymorpha (Less) Cabr. ssp. floccosa Cabr. trunk bark, guided by antiproliferative assays on 10 human cancer cell lines and the VERO cell line, yielded six known compounds identified as the triterpene bauerenyl acetate, the guaianolide 11α,13-dihydrozaluzanin C and the dimeric guaianolides 10-desoxygochnatiolide A, gochnatiolide A, 8-hydroxi-10-desoxygochnatiolide A and 8-hydroxigochnatiolide A. Extracts, fractions of extracts and isolated compounds were tested in vitro agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…The chemopreventive potential, as well as the cell cycle arrest capacity, of M. polymorpha supports the results of Strapasson et al (2012), who reported anticarcinogenic activity in cultured tumor cells. In addition, Martins et al (2015) reported that Walker-256 tumor growth was inhibited when rats were treated with a dichloromethane fraction of M. polymorpha.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The chemopreventive potential, as well as the cell cycle arrest capacity, of M. polymorpha supports the results of Strapasson et al (2012), who reported anticarcinogenic activity in cultured tumor cells. In addition, Martins et al (2015) reported that Walker-256 tumor growth was inhibited when rats were treated with a dichloromethane fraction of M. polymorpha.…”
Section: Discussionsupporting
confidence: 87%
“…Sesquiterpene lactones, such as 11αH-13-dihydrozaluzanin C, 8-hydroxigochnatiolide A, 8-hydroxi-10-desoxigochnatiolide A, gochnatiolide A, gochnatiolide B, and 10-desoxygochnatiolide A, are considered the bioactive components of MPEE (Piornedo et al, 2011;Strapasson et al, 2012;Martins et al, 2015). Sesquiterpene lactones may interfere with some key biological processes, such as cell signaling, proliferation, and death/apoptosis, and mitochondrial respiration, all of which constitute the molecular basis of their diverse pharmacological activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our research group described the antineoplastic activity of this extract, its fractions, and isolated compounds in both in vitro and in vivo assays (Strapasson et al, 2012;Martins et al, 2015). The in vivo assays revealed that the dichloromethane fraction of this medicinal plant reduces the growth of Walker 256 carcinosarcoma (Martins et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the plant is rich in sesquiterpene lactones, sesquiterpenes, diterpenes, triterpenes, flavonoids, coumarins, phenolic compounds, and essential oils (Strapasson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%